Conceptual framework to define management strategies for silvopastoral systems in native forests - Peri, Pablo Luis (2022)
Most of the native forests in Argentina are used for livestock production with little sustainable silvopastoral management. Our objective here is to discuss different management strategies where natural and human capital are combined to co-produce cosystem services (ES) provided by silvopastoral systems in native forests, interacting with different ecosystem functions and biodiversity. Also, we provide perspectives that should be analyzed in a context of socio-ecological approaches in agro-forestry landscapes. Four types of theoretical strategies are proposed (win-win, win-lose, lose-win and lose-lose), which define the social-ecological and economic thresholds that determine the provision of ES and biodiversity in the long term. The evidence of the win-lose strategy occurs when the silvopastoral systems are managed mainly to increase economic profitability through increments in forage biomass aimed to increase livestock production in the medium and long term. Deferred deforestation was presented as a typical example of lose-lose strategy in the Chaco region based on short-term management strategies by only obtaining commodities (crops or livestock products) without considering the negative interactions with other ES and loss of biodiversity. The information provided in this work should assist stakeholders and researchers to identify thresholds of economic profitability and ecological resilience in ecosystems under management. The proposed approaches provide a utilitarian vision of ecosystem services and key aspects of social-ecological resilience.